'Landscape In Miniature'—The use of the gum leaf as a painting support in colonial Victoria. Issue 2 (3rd July 2017) - Fry, Caroline; Kowalski, Vanessa; Nunn, Catherine
Abstract : The paper examines the history of the use of the gum leaf as a support for oil paintings in colonial Australia, with a focus on the conservation treatment of four paintings by artist Alfred William Eustace from the Albury City Gallery Collection. The paper presents some historic background and describes the technical analysis of the material components of these unique paintings, their condition and the conservation treatment undertaken in preparation for exhibition.